2016
DOI: 10.4244/eijy15m11_07
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ticagrelor monotherapy versus standard dual antiplatelet therapy followed by aspirin monotherapy in patients undergoing biolimus-eluting stent implantation: rationale and design of the GLOBAL LEADERS trial

Abstract: Aims: The GLOBAL LEADERS trial is a superiority study in patients undergoing percutaneous coronary intervention, with a uniform use of Biolimus A9-eluting stents (BES) and bivalirudin. GLOBAL LEADERS was designed to assess whether a 24-month antithrombotic regimen with ticagrelor and one month of acetylsalicylic acid (ASA), compared to conventional dual antiplatelet therapy (DAPT), improves outcomes.Methods and results: Patients (n >16,000) are randomised (1:1 ratio) to ticagrelor 90 mg twice daily for 24 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 33 publications
0
126
0
6
Order By: Relevance
“…Until recently, there were only limited data addressing this issue from beyond the periprocedural phase to 1 year. By now, two studies addressing such a step-down concept have finished recruitment: Testing Responsiveness to Platelet Inhibition on Chronic Antiplatelet Treatment For Acute Coronary Syndromes Trial (TROPICAL-ACS) (NCT01959451) with a stepdown from prasugrel to clopidogrel after the peri-interventional phase in acute MI; and GLOBAL-LEADERS (NCT01813435) 146 with a step-down from DAPT to single antiplatelet therapy with ticagrelor beyond the first month after PCI in an all-comers cohort with DES. The risks and benefits of shortening DAPT to 3 months or even shorter is another area with limited evidence.…”
Section: Iia Cmentioning
confidence: 99%
“…Until recently, there were only limited data addressing this issue from beyond the periprocedural phase to 1 year. By now, two studies addressing such a step-down concept have finished recruitment: Testing Responsiveness to Platelet Inhibition on Chronic Antiplatelet Treatment For Acute Coronary Syndromes Trial (TROPICAL-ACS) (NCT01959451) with a stepdown from prasugrel to clopidogrel after the peri-interventional phase in acute MI; and GLOBAL-LEADERS (NCT01813435) 146 with a step-down from DAPT to single antiplatelet therapy with ticagrelor beyond the first month after PCI in an all-comers cohort with DES. The risks and benefits of shortening DAPT to 3 months or even shorter is another area with limited evidence.…”
Section: Iia Cmentioning
confidence: 99%
“…Ongoing studies are examining novel strategies with DAPT including different treatment regimens, shorter DAPT durations in ACS and novel stent platforms. The GLOBAL LEADERS (NCT01813435),21 which is the largest of the ongoing clinical trials with DAPT, examines the efficacy of DAPT with ticagrelor plus aspirin for 1 month followed by 23 months of single treatment with ticagrelor compared with the standard 12 months of DAPT followed by aspirin monotherapy in patients after biolimus DES implantation. The TWILIGHT (NCT02270242) trial examines the safety of DAPT with ticagrelor and aspirin for 3 months and then ticagrelor alone versus the same DAPT regimen for 12 months.…”
Section: Future Perspectivementioning
confidence: 99%
“…Glycoprotein IIb/IIIa antagonists (eptifibatide, abciximab, and tirofiban) are also widely used in ACS patients with complicated lesions and high-risk AST; clinical observations showed that glycoprotein IIb/IIIa antagonists could effectively prevent AST [1,60]. Nowadays, several novel antiplatelet and anticoagulation drugs, such as prasugrel, dabigatran, apixaban and abciximab, ticagrelor and rivaroxaban, are paving their way for clinical use through randomized trials (GEMINI-ACS study and GLOBAL LEADERS trial); their applications in future clinical practice might enrich the therapy options and be helpful for more effective prevention and treatment of AST [61,62]. …”
Section: Prevention and Clinical Management Of Ast: Current Concepts mentioning
confidence: 99%